A Bidirectional Mendelian Randomization Study Investigating the Causal Relationship Between Ankylosing Spondylitis and Chronic Obstructive Pulmonary Disease - Pan D; Dai X; Li P; Xue L (International Journal of COPD)
Di Pan,1,2 Xiaoling Dai,3 Pan Li,4 Luan Xue1 1Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Shanghai Putuo Traditional Chinese Medicine Hospital, Shanghai, People’s Republic of China; 4Longhua Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Luan Xue; Xiaoling Dai, Email 610725556@qq.com; 553137182@qq.comBackground: Previous studies have found an association between ankylosing spondylitis (AS) and chronic obstructive pulmonary disease (COPD); however, no research has investigated this relationship using Mendelian randomization (MR).Methods: This study employed a bidirectional two-sample MR approach to assess the causal connection between AS and COPD. The analysis utilized publicly available statistics on AS and COPD from the Genome-wide Association Study (GWAS). The primary MR method employed was Inverse-Variance Weighting (IVW), supplemented by additional MR methods such as weighted median, MR-Egger, simple mode, and weighted mode. Sensitivity analyses were also performed to evaluate the impact of heterogeneity and pleiotropy on the MR results.Results: The study included two datasets related to AS (ebi-a-GCST005529 and ukb-a-88) and two datasets related to COPD (ebi-a-GCST90018807 and finn-b-J10_COPD). In our forward MR, the analysis of ebi-a-GCST005529 dataset against ebi-a-GCST90018807 dataset showed that AS was associated with an increased risk of COPD (OR = 1.1326, 95% CI = 1.0181– 1.2600, P = 0.0221). However, there was no causal relationship between AS and COPD in the rest of the dataset analyses. In reverse MR analysis, no causal effect between COPD and AS was found among the datasets.Conclusion: Our research provided partial evidence to support the viewpoint that AS may increase the prevalence of COPD. AS may be a risk factor for COPD, however, further studies are needed to validate these results and elucidate the underlying mechanisms.Keywords: ankylosing spondylitis, chronic obstructive pulmonary disease, Mendelian randomization, causal relationship